Ventilator-associated pneumonia: incidence, microbial etiology and antimicrobial resistance profile - Alvares, Flávia Allegretti (2022)
Background and Objectives: Infections caused by multi-drug resistant microorganisms have a great clinical and economic impact. The present study proposed to determine and assess ventilator-associated pneumonia (VAP) incidence in an Intensive Care Unit (ICU), to establish the profile of hospitalized patients and to determine the frequency of microorganisms isolated as well as their antimicrobial resistance profile. Methods:  A descriptive, documental study, with a quantitative approach, carried out at a teaching hospital. Participants were all individuals admitted to the General ICU who developed VAP in 2018 and 2019. Results: During the study, 146 patients were diagnosed with VAP, with an incidence of 23.66/1000 patient-days on mechanical ventilation. The median age of patients was 52.5 years and most of them were man. One hundred and eight microorganisms were isolated in cultures, the majority being gram-negative bacteria. Non-fermenting bacteria were the most frequent (n=46; 42.6%), followed by enterobacteria (n=42; 38.9%). Staphylococcus aureus was the most frequent microorganism among gram-positive (n=17; 15.7%). The most frequent multi-drug resistant bacteria were Acinetobacter baumannii and Enterobacter spp. No microorganism showed colistin and vancomycin resistance. Patients infected with multidrug-resistant bacteria were hospitalized longer when compared to other patients. Conclusions: VAP incidence was high. The knowledge of the etiologic agents of VAP and their antimicrobial resistance profile is fundamental to support the elaboration of institutional treatment protocols as well as assist in empirical antibiotic therapy.